Does wealth entirely depend on inclusive institutions and pluralist politics? a review of daron acemoglu and james a. robinson, why nations fail (2013)
The authors of the book reviewed here need no introducing. They areamongst the most-frequently cited scholars in the social sciences. Theywrote many highly influential articles, as a rule together with Simon Johnson,and already published a book together in 2006. Their book needsno further praise; it opens with jacket quotes of praise by no fewerthan five Nobel-prize winners in economics, and by amongst othersJared Dia- mond, Niall Ferguson, Francis Fukuyama, Joel Mokyr, DaniRodrik and Ian Morris. It would not make much sense to add my humbleeulogy to such distinguished recommendation. I will therefore mainlyconfine myself to critical comments. Not because one can only criticizethe book, although I am less impressed than the ‘reviewers’ I justreferred to, but because amidst all that praise some critical counterpoisefrom an economic histo- rian can do no harm.